2018
DOI: 10.3389/fimmu.2018.01118
|View full text |Cite
|
Sign up to set email alerts
|

IL-9 Deficiency Promotes Pulmonary Th17 Response in Murine Model of Pneumocystis Infection

Abstract: IntroductionPneumocystis pneumonia (PCP) remains a severe complication with high mortality in immunocompromised patients. It has been well accepted that CD4+ T cells play a major role in controlling Pneumocystis infection. Th9 cells were the main source of IL-9 with multifaced roles depending on specific diseases. It is unclear whether IL-9/Th9 contributes to the immune response against PCP. The current study aims to explore the role of IL-9 and the effect of IL-9 on Th17 cells in murine model of PCP.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…Allergic diseases are Th2-polarized diseases [36], whereas psoriasis is a Th17 disease, in general speaking, but could be a Th9-polarized disease in the gut [36,37]. This transition may explain why allergic skin disease does not coexist with PSO in our cohort, but whether the Th9 links between the Th2 [38] and Th17 [39] pathogeneses need to be further investigated. Fig.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Allergic diseases are Th2-polarized diseases [36], whereas psoriasis is a Th17 disease, in general speaking, but could be a Th9-polarized disease in the gut [36,37]. This transition may explain why allergic skin disease does not coexist with PSO in our cohort, but whether the Th9 links between the Th2 [38] and Th17 [39] pathogeneses need to be further investigated. Fig.…”
Section: Discussionmentioning
confidence: 84%
“…Allergic diseases are Th2-polarized diseases [ 36 ], whereas psoriasis is a Th17 disease, in general speaking, but could be a Th9-polarized disease in the gut [ 36 , 37 ]. This transition may explain why allergic skin disease does not coexist with PSO in our cohort, but whether the Th9 links between the Th2 [ 38 ] and Th17 [ 39 ] pathogeneses need to be further investigated. Another explanation is that IL17E, also known as IL25, could propagate production of IL-4 and IL-13 in different organs, which stimulate the expansion of eosinophils [ 40 ], and link between allergic disease and psoriatic disease.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, Th17 cells are also thought to produce IL-9 [44]; how this influences Th17 responses to Pneumocystis remains to be determined. Investigations by Li et al suggested that, despite Pneumocystis clearance in wild-type (WT) and IL-9-deficient mice, IL-9 deficiency may actually lower lung burden and promote pulmonary Th17 responses in the early stages of infection [45]. Th1 and Th2 have also been implicated in host protection against Pneumocystis .…”
Section: Lymphocytes: Cd4+ T Cells Cd8+ T Cells and B Cellsmentioning
confidence: 99%
“…Additionally, the IL-17/IL-23 axis was capable of extending the Th17 effector response 19, and Th17 cells are involved in the immune response during P. jirovecii infection 20. More recently, IL-9 -/- mice showed reduced P. murina burden in the lungs 21. The presence of CD8 + T cells in response to P. jirovecii infection may also be deleterious 22.…”
Section: Introductionmentioning
confidence: 99%